2013
DOI: 10.1103/physrevlett.110.047401
|View full text |Cite
|
Sign up to set email alerts
|

Optical Probing of Ultrafast Electronic Decay in Bi and Sb with Slow Phonons

Abstract: Type of publicationArticle (peer-reviewed) Access to the full text of the published version may require a subscription. Rights

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
131
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 65 publications
(143 citation statements)
references
References 19 publications
12
131
0
Order By: Relevance
“…Thus, the observed relaxation rate -of the order of several femtosecond -for the decay of the E g force in Li et al 45 is consistent with a plasma cooling time (and associated lattice heating time) of a few picoseconds. We note that, whereas the contribution to the electronhole recombination rate arises only in the energy region where the conduction and valence bands overlap (plus approximately 10 meV for the energy of the phonon participating in the recombination process), the contribution to plasma-lattice heat transfer when the plasma is hotter than the lattice arises from all bands.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Thus, the observed relaxation rate -of the order of several femtosecond -for the decay of the E g force in Li et al 45 is consistent with a plasma cooling time (and associated lattice heating time) of a few picoseconds. We note that, whereas the contribution to the electronhole recombination rate arises only in the energy region where the conduction and valence bands overlap (plus approximately 10 meV for the energy of the phonon participating in the recombination process), the contribution to plasma-lattice heat transfer when the plasma is hotter than the lattice arises from all bands.…”
Section: Discussionsupporting
confidence: 57%
“…Indeed, this is in good agreement with the momentum relaxation time inferred in recent experiments comparing spontaneous and impulsive stimulated Raman scattering in Bi and Sb, corresponding to the decay rate of the electronic forces driving the low-symmetry E g mode . In these experiments, a decay time, 1/γ p ≈ 5 − 10 fs is observed for the E g force at room temperature for Bi 45 . On the other hand, taking a typical optical phonon energy in Bi to be approximately 10 meV, we can use Eq.…”
Section: A Momentum and Energy Relaxation Of The Hot Plasmamentioning
confidence: 88%
“…However, the model optical pulse used in these calculations was more than an order of magnitude higher fluence and significantly shorter duration than that used in the experiment. Moreover, the lifetime of the E g driving force due to final-state scattering [7] was not accounted for, leading to results that do not correspond directly to experiment.…”
mentioning
confidence: 99%
“…Zijlstra et al [13] suggested that coherent E g phonon motion is a result of anharmonic coupling to the DECP-driven A 1g mode, although the E g amplitude estimated by this mechanism is much smaller than that observed. Recent experimental work [7], which measured the decay rate of the force driving the E g mode in bismuth, found that the E g force lifetime varies from 13 fs at low temperature to 2 fs at room temperature and suggested that this low-symmetry force may arise from an initial unbalanced occupation of symmetry-equivalent regions in the Brillouin zone, which rapidly decays via electron-phonon scattering to a fully symmetric occupation. A similar conclusion was also reached in recent x-ray diffraction measurements of the E g mode in bismuth [5], where the magnitude of the atomic displacements associated with the E g phonon was directly measured.…”
mentioning
confidence: 99%
See 1 more Smart Citation